Analisis Faktor-Faktor yang Mempengaruhi Keterlambatan Laporan Audit pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Kennardi Tanujaya; sherly sherly (Jurnal Bina Akuntansi, 2023)
This study aims to determine the effect of company size variables, market-tobook ratio, number of reporting segments, leverage, business risk, management incentives, best practice audit committees, independence of the board of directors, and size of the Public Accounting Firm (KAP) on late reports. audits. The objects in this study are annual reports and financial reports of companies that have been audited and listed on the Indonesia Stock Exchange in the period 2017 to 2021. The method used is purposive sampling. The sample of thisresearch is 453 companies. Processing of the data collected was carried out using panel regression data analysis techniques. The results showed that the number of reporting segments, business risk, and best practice audit committees had a significant effect on late audit reports, while the market-to-book ratio,leverage, management incentives and independence of the board of directors had no significant effect on late audit reports. The rest, namely company size and KAP size, did not show a significant effect on the delay in the audit report.